Never too little: Grip and lift forces following probabilistic weight cues in patients with writer's cramp. Issue 12 (December 2021) - Zeuner, Kirsten E.; Knutzen, Arne; Granert, Oliver; Trampenau, Leif; Baumann, Alexander; Wolff, Stephan; Jansen, Olav; van Eimeren, Thilo; Kuhtz-Buschbeck, Johann P.
Graphical abstract: Highlights: Patients with writer's cramp do not respond to probabilistic cues indicating that an object will probably be light in a grip-lift task. The results fit with the pathophysiological concept of a hyperfunctional direct basal ganglia pathway in writer's cramp patients. Writer's cramp patients' brain activity does not differ significantly from that of control subjects in the grip-lift task with probabilistic cues. Abstract: Objective: Planning of voluntary object-related movements requires the estimation of the most probable object properties. We investigated how 14 writer's cramp (WC) patients compared to 14 controls use probabilistic weight cues in a serial grip-lift task. Methods: In every grip-lift trial, an object of either light, medium or heavy weight had to be grasped and lifted after a visual cue gave a probabilistic prediction of the object weights (e.g. 32.5% light, 67.5% medium, 0 % heavy). We determined peak (1) grip force GF, (2) load force LF, (3) grip force rate GFR, (4) load force rate LFR, while we registered brain activity with functional magnetic resonance imaging. Results: In both groups, GFR, LFR and GF increased when a higher probability of heavy weights was announced. When a higher probability of light weights was indicated, controls reduced GFR, LFR and GF, while WC patients did not downscale their forces. There were no inter-group differences in blood oxygenation level dependent activation. Conclusions: WC patients could not utilize the decision range in motor planning and adjust their force in a probabilistic cued fine motor task. Significance: The results support the pathophysiological model of a hyperfunctional dopamine dependent direct basal ganglia pathway in WC.